Artificial reefs in the North –East Atlantic area: Present situation, knowledge gaps and future perspectives. (1st November 2021) - Reis, Bianca; van der Linden, Pieter; Pinto, Isabel Sousa; Almada, Emanuel; Borges, Maria Teresa; Hall, Alice E.; Stafford, Rick; Herbert, Roger J.H.; Lobo-Arteaga, Jorge; Gaudêncio, Maria José; Tuaty-Guerra, Miriam; Ly, Océane; et al.
Abstract: Artificial reefs have been deployed in multiple regions of the world for different purposes including habitat restoration and protection, biodiversity and fish stock enhancement, fisheries management and recreation. Artificial reefs can be a valuable tool for ecosystem protection and rehabilitation, helping mitigate the effects of anthropogenic impacts that we face today. However, knowledge on artificial reefs is unevenly distributed worldwide, with some regions having much more quality information available and published (e.g. European Mediterranean Sea area), while others, for instance the North-East Atlantic area, do not. Here, we provide a characterization of purposely built artificial reefs in North-East Atlantic area based on all available literature (i.e. research papers and reports), highlighting the needs and gaps that are vital for establishing future perspectives for artificial reef deployment and research. In the North-East Atlantic area, sixty-one purposely built artificial reefs have been deployed since 1970, mostly between the years 1990–2009, with Spain being the country with the highest number of artificial reefs. The most reported purpose for their deployment is fisheries productivity and habitat/species protection, although, most artificial reefs are multipurpose in order to maximise the benefits of a given financial investment. The majority of artificial reefs were submerged at < 50 m, mainly between 10 and 20 m of depth. The most used designs were cubic blocks and complex designs made by an array of combined shapes, which mostly consist of concrete (79%). From all the analysed data on artificial reefs, 67% of the cases reported surveys to assess biodiversity after the deployment. However, in 26% of those cases, data was not available. When data was available, only 31% of cases reported long-term biomonitoring surveys (3 years or more). Based upon these findings, we noticed a general lack of scientifically robust data, including records of species and abundance of both fish and invertebrates, as well as macroalgae, preventing an adequate determination of the best balance between shape, construction material and bio-colonization. Critiques and suggestions are discussed in the light of currently available data in order to perform more efficient research, evaluation and functioning of future artificial reefs. Highlights: 61 artificial reefs have been in North-East Atlantic area, mostly between 1990 and 2009. Most reported purposes are fisheries enhancement and habitat/species protection. Concrete cubic blocks and complex designs (array of combined shapes) were most used. General insufficient or non-adequate biodiversity surveys (pre/post deployment).